2022
DOI: 10.3920/jiff2021.0038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rearing system and microbial inoculation on black soldier fly larvae growth and microbiota when reared on agri-food by-products

Abstract: Black soldier fly larvae (BSFL) are widely used in recycling and upcycling of nutrients in agri-food by-products, but low and inconsistent BSFL rearing performance (i.e. larval growth, bioconversion rate, and substrate reduction) has been identified as a key challenge. The aims of this research were two-fold: (1) validate an existing closed rearing system design; and (2) assess whether a microbial inoculum derived from the rearing residue increases rearing performance. In controlled bench-scale experiments, BS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Identifying beneficial cultivable or transmittable microbial candidates depends on their characteristics and the nature of their host association. Specific microbial inoculations may positively influence production efficiency [ 107 , 108 , 109 , 110 ]. Yet, despite no clear evidence for vertical maternal imprinting for the time being [ 111 ], the BSF may possess such specific symbioses known from other insect systems (e.g., [ 112 , 113 ]), which thus may be amenable to fostering alternative inheritable solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying beneficial cultivable or transmittable microbial candidates depends on their characteristics and the nature of their host association. Specific microbial inoculations may positively influence production efficiency [ 107 , 108 , 109 , 110 ]. Yet, despite no clear evidence for vertical maternal imprinting for the time being [ 111 ], the BSF may possess such specific symbioses known from other insect systems (e.g., [ 112 , 113 ]), which thus may be amenable to fostering alternative inheritable solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the larval transamination pathway, the microbial biomass pathway could reduce manure NH 3 emissions if NH 3 -N assimilation in larvae is maximized via rearing conditions. For instance, substrates inoculated with microbes can increase both bioconversion and larval weights (Mazza et al, 2020;Wong et al, 2021;Xiao et al, 2018), although this is not always the case (Gold et al, 2021;Hasnol et al, 2020). Future assessments should elucidate if increased bioconversion due to specific microbial inocula is correlated with larger NH 3 -N assimilation in manure-based diets.…”
Section: Opportunities and Outlookmentioning
confidence: 99%
“…While the larvae can consume many different types of biowaste, the nutritional composition of the substrate has a great impact on BSFL composting efficiency, measured as e.g., waste-to-biomass conversion efficiency (BCE), final larval weight, waste reduction efficiency, and larval survival during composting (Kawasaki et al, 2019;Lalander et al, 2019;Gold et al, 2020). To achieve high BCE (≥12 % dry matter (DM)) and high final larval weight (≥200 mg larva −1 ), the substrate needs to have a sufficiently high protein content (≥15% DM ) (Lalander et al, 2019;Gold et al, 2020) and a balanced protein to carbohydrate ratio (~1:1) (Cammack and Tomberlin, 2017;Gold et al, 2020), while the fiber and lipid content should not be too high (Gold et al, 2021;Lopes et al, 2020;Rehman et al, 2017). For example, low BCE (<12% DM ) has been reported when treating vegetable and fruit waste with a low protein content (≤13% DM ) (Isibika et al, 2019;Jucker et al, 2017;Lalander et al, 2019;Nyakeri et al, 2017) and no BSFL survival has been reported when composting pure fish waste with a high fat content (>50% DM ) (Lopes et al, 2020;Isibika et al, 2021).…”
Section: Introductionmentioning
confidence: 99%